Does authentic leadership develop inclusive classrooms: a model examination?. Issue 4 (14th March 2022) - Srivastava, Anugamini Priya; Shree, Sonal; Agarwal, Sucheta
Abstract : Purpose: The present study aims to statistically prove the theoretical model on inclusive higher education provided by Srivastava and Shree (2019), which analyzes the effect of authentic leadership (AL) on inclusive classrooms (ICs) with the intervening role of academic optimism (AO) and art-based innovation pedagogies. Design/methodology/approach: This current study collected data through a questionnaire method from higher education faculty and the faculty's immediate leaders. Statistical methods like descriptive analysis, confirmatory factor analysis (CFA) and multiple regression analysis were conducted to evaluate the variables, model fit and hypothesis, respectively. Findings: The results indicated a positive effect of AL on ICs via the partial mediating role of AO. However, unlike the proven theoretical model, the moderating role of art-based innovation pedagogy between AO and the IC was not supported. Originality/value: The implications of this study advanced the theoretical aspect of the model while providing managerial suggestions that can be applied to support the development of ICs in educational institutions.